Primary chronic osteomyelitis in the mandible: a conservative approach. (3rd April 2014) - Agarwal, Anuja; Kumar, Nishant; Tyagi, Amit; De, Nayana
Abstract : Primary chronic osteomyelitis of the jaw is an uncommon non-suppurative, chronic inflammatory disease of unknown origin. It can manifest as early or adult onset and is characterised by lack of pus formation, fistula or bony sequestra formation. A 28-year-old woman presented with swelling on the left side of her mandible. On the basis of clinical, radiological and histological findings, primary chronic osteomyelitis was diagnosed. Surgical decortication and contouring of the affected bone was performed and no signs of recurrence were seen at 2-year follow-up. Hence we emphasise the importance of decortication over peripheral or segmental resection of the jaw for the treatment of primary chronic osteomyelitis since this procedure is less aggressive and more functionally and aesthetically acceptable.